2007
DOI: 10.1177/0010414007303651
|View full text |Cite
|
Sign up to set email alerts
|

Parliamentary Cycles and Party Switching in Legislatures

Abstract: This article examines politicians' changes of party labels during the life of a legislature. The authors view a legislator's choice of party as a strategic decision recurring throughout the parliamentary cycle. In their approach, individuals are open to switching parties as they pursue goals specific to the stage in the parliamentary cycle. Analyzing Italy and Russia, they identify among legislators in both countries patterns of heightened switching for office benefits, policy advantage, and vote seeking at di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(51 citation statements)
references
References 21 publications
0
50
0
1
Order By: Relevance
“…Hence I treat legislative parties as endogenous coalitions (Mershon and Shvetsova, 2005;cf. Elsewhere I show that MPs act in ways consistent with this notion; and yet MPs' switching behavior is also deterred by the electoral costs they expect to be attached to the switch (Mershon and Shvetsova, 2008a, 2008b, 2009. Further, MPs themselves derive advantage from treating their legislative party affiliation as endogenous, choosing whatever party has more to offer them at any given time.…”
Section: Links Between Legislative Party Switching and Executive Coalmentioning
confidence: 84%
See 2 more Smart Citations
“…Hence I treat legislative parties as endogenous coalitions (Mershon and Shvetsova, 2005;cf. Elsewhere I show that MPs act in ways consistent with this notion; and yet MPs' switching behavior is also deterred by the electoral costs they expect to be attached to the switch (Mershon and Shvetsova, 2008a, 2008b, 2009. Further, MPs themselves derive advantage from treating their legislative party affiliation as endogenous, choosing whatever party has more to offer them at any given time.…”
Section: Links Between Legislative Party Switching and Executive Coalmentioning
confidence: 84%
“…Answers to this question are not yet clear, despite the achievements of recent studies of party switching (e.g., Desposato, 2006;Heller and Mershon, 2003, 2009a, 2009b, 2009dLaver and Benoit, 2003;Mershon and Shvetsova, 2008a, 2008b, 2009Reed and Scheiner, 2003). Answers to this question are not yet clear, despite the achievements of recent studies of party switching (e.g., Desposato, 2006;Heller and Mershon, 2003, 2009a, 2009b, 2009dLaver and Benoit, 2003;Mershon and Shvetsova, 2008a, 2008b, 2009Reed and Scheiner, 2003).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Not surprisingly, previous research has found a strong connection between electoral considerations and party switching. Specifically, legislators are more likely to switch at the beginning of the legislative term since voters tend to have short memories (Mershon & Shvetsova 2008, Mershon & Shvetsova 2013, and they prefer to affiliate with popular and up-and-coming parties to capitalize on the party's high approval ratings (Heller & Mershon 2005, Kato & Yamamoto 2009, O'Brien & Shomer 2013, Reed & Scheiner 2003. Likewise, legislators are more likely to switch in districts with low educated constituencies, where clientelism is more prevalent and politicians can secure electoral support with goods and services.…”
Section: Theorymentioning
confidence: 99%
“…The literature on party unity, cohesion and discipline is voluminous. For representative studies, see the following works: Becher and Sieberer (2008); Bowler, Farrell, and Katz (1999); Carey (2007); Desposato (2006); Grofman, Evald, and Taagepera (2000); Hazan (2003); Mershon (2005, 2008); Hix (2004); Mershon and Shvetsova (2008); Montgomery (1999); Nokken and Poole (2004); Ö zbudun (1970); Sieberer (2006). 2.…”
Section: Notesmentioning
confidence: 99%